Perioperative Single-Donor Platelet Apheresis and Red Blood Cell Transfusion Impact on 90-Day and Overall Survival in Living Donor Liver Transplantation - Wei Zheng; Kang-Mei Zhao; Li-Hui Luo; Yang Yu; Sheng-Mei Zhu (Chinese Medical Journal, 2018)
Background: Although many previous studies have confirmed that perioperative blood transfusion is associated with poor outcomes after liver transplantation (LT), few studies described the influence of single-donor platelet apheresis transfusion in living donor LT (LDLT). This study aimed to assess the effect of blood products on outcomes for LDLT recipients, focusing on apheresis platelets. Methods: This retrospective study included 126 recipients who underwent their first adult-to-adult LDLT. Twenty-four variables including consumption of blood products of 126 LDLT recipients were assessed for their link to short-term outcomes and overall survival. Kaplan-Meier survival curve and the log-rank test were used for recipient survival analysis. A multivariate Cox proportional-hazard model and a propensity score analysis were applied to adjust confounders after potential risk factors were identified by a univariate Cox analysis. Results: Patients who received apheresis platelet transfusion had a lower 90-day cumulative survival (78.9% vs. 94.2%, P = 0.009), but had no significant difference in overall survival in the Cox model, compared with those without apheresis platelet transfusion. Units of apheresis platelet transfusion (hazard ratio [HR] = 3.103, 95% confidence interval [CI]: 1.720–5.600, P < 0.001) and preoperative platelet count (HR = 0.170, 95% CI: 0.040–0.730, P = 0.017) impacted 90-day survival independently. Multivariate Cox regression analysis also found that units of red blood cell (RBC) transfusion (HR = 1.036, 95% CI: 1.006–1.067, P = 0.018), recipient's age (HR = 1.045, 95% CI: 1.005–1.086, P = 0.025), and ABO blood group comparison (HR = 2.990, 95% CI: 1.341–6.669, P = 0.007) were independent risk factors for overall survival after LDLT. Conclusions: This study suggested that apheresis platelets were only associated with early mortality but had no impact on overall survival in LDLT. Units of RBC, recipient's age, and ABO group comparison were independent predictors of long-term outcomes.